Hybrid heart valves with VEGF-loaded zwitterionic hydrogel coating for improved anti-calcification and re-endothelialization. (15th December 2022) - Tong, Qi; Sun, Ao; Wang, Zhengjie; Li, Tao; He, Xinye; Qian, Yongjun; Qian, Zhiyong
Abstract: With the aging of the population in worldwide, valvular heart disease has become one of the most prominent life-threatening diseases in human health, and heart valve replacement surgery is one of the therapeutic methods for valvular heart disease. Currently, commercial bioprosthetic heart valves (BHVs) for clinical application are prepared with xenograft heart valves or pericardium crosslinked by glutaraldehyde. Due to the residual cell toxicity from glutaraldehyde, heterologous antigens, and immune response, there are still some drawbacks related to the limited lifespan of bioprosthetic heart valves, such as thrombosis, calcification, degeneration, and defectiveness of re-endothelialization. Therefore, the problems of calcification, defectiveness of re-endothelialization, and poor biocompatibility from the use of bioprosthetic heart valve need to be solved. In this study, hydrogel hybrid heart valves with improved anti-calcification and re-endothelialization were prepared by taking decellularized porcine heart valves as scaffolds following grafting with double bonds. Then, the anti-biofouling zwitterionic monomers 2-methacryloyloxyethyl phosphorylcholine (MPC) and vascular endothelial growth factor (VEGF) were utilized to obtain a hydrogel-coated hybrid heart valve (PEGDA-MPC-DHVs@VEGF). The results showed that fewer platelets and thrombi were observed on the surface of the PEGDA-MPC-DHVs@VEGF. Additionally, the PEGDA-MPC-DHVs@VEGF exhibited excellent collagen stability, biocompatibility and re-endothelialization potential. Moreover, less calcification deposition and a lower immune response were observed in the PEGDA-MPC-DHVs@VEGF compared to the glutaraldehyde-crosslinked DHVs (Glu-DHVs) after subcutaneous implantation in rats for 30 days. These studies demonstrated that the strategy of zwitterionic hydrogels loaded with VEGF may be an effective approach to improving the biocompatibility, anti-calcification and re-endothelialization of bioprosthetic heart valves. Graphical abstract: Hybrid heart valves with VEGF-loaded zwitterionic hydrogel coating exhibit good hemocompatibility, decrease calcium deposition and promote adhesion of endothelial cells. Thus, strategy of coating with zwitterionic hydrogel and loaded VEGF may be an effective and potential approach to improve biocompatibility, anti-calcification and re-endothelialization of bioprosthetic heart valves. Image 1 Highlights: A new and promising strategy of overcoming defects of bioprosthetic heart valves. The zwitterionic hydrogel with VEGF is utilized to improve anti-calcification and re-endothelialization properties of heart valves. The hybrid heart valves with a VEGF-loaded zwitterionic hydrogel coating exhibits excellent biocompatibility.